PENGARUH PENAMBAHAN MALTODEKSTRIN PADA KOMPOSISI MINUMAN SERBUK INSTAN HASIL OLAHAN BIJI NANGKA (Arthocarpus Heterophyllus Lamk.) SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MATERI BIOTEKNOLOGI KELAS XII SMA - Nurhayati Nurhayati; Imam Mahadi; Darmawati Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This study aims to determine the effect of the addition of maltodextrin on the composition of instant powder drinks produced by jackfruit seeds (Arthocarpus Heterophyllus Lamk.) As a design of student worksheet (LKPD) for X11 grade biotechnology material. This study used a factorial Completely Randomized Design (RAL) method consisting of 5 treatments and 3 replications, namely protein content using (M0 = 0; M1 = 5%; M2 = 10%; M3 = 15%; M4 = 20%; and M5 = 25%), carbohydrate treatment (M0 = 0; M1 = 5%; M2 = 10%; M3 = 15%; M4 = 20%; and M5 = 25%), levels fat (M0 = 0; M1 = 5%; M2 = 10%; M3 = 15%; M4 = 20%; and M5 = 25%), as well as organoleptic tests (descriptive and hedonic). The results showed that the addition of maltodextrin to the levels of protein, fat, carbohydrate after the results of a variance test (Variant Analysis) showed that the addition of maltodextrin in the composition of instant powder drinks produced by jackfruit seeds had no significant effect. Then the DMRT test was not carried out at the level of 5%. However, the highest and best levels were obtained from protein, carbohydrate, fat, and organoleptic content, namely in the M5 treatment (25%). All scientific facts from the research can be used to design student worksheets (LKPD) on conventional biotechnology materials in class XII of high school using the project based learning (PPA) model. However, before the design of the LKPD is used on a broader scale it is recommended that a feasibility test be carried out on a limited scale.Key Words: jackfruit seeds, maltodextrin, student worksheet (LKPD).